The importance of innovation in reshoring processes: a literature review (Encuentros, 2023)
Some global phenomena such as globalization, the US-China trade war, and Covid-19, have led companies around the world to consider reshoring strategies – backshoring and/or nearshoring – with the purpose of configuring more efficient supply chains and less susceptible to these events that generate disruptions in the world economy. Based on the foregoing, research has been developed in order to determine the factors that motivate companies to make reshoring decisions, finding the innovation factor as reiterative in many of these research works, in fact, it has been found that It is a factor that influences other factors. In this sense, this article aims to recognize the importance of innovation in companies’ reshoring processes, through a narrative literature review where some background on location decisions is explored, the main relocation trends are described, and the importance of innovation within these relocation processes is established based on the work of different theoretical references. Among the main results of this review, it was found that i) innovation in transportation systems led many companies to have broader geographic scales to locate their operation and configure global supply chains; ii) access to innovation is a factor that is usually taken into account for the creation of reshoring government policies; iii) Innovation is a factor with a degree of transversality since it affects other variables that are taken into account for reshoring.
Keywords: Innovation, reshoring, nearshoring, backshoring, literature review, Covid-19.